High frequency of Tropheryma whipplei in culture-negative endocarditis - Geißdörfer, Walter; Moos, Verena; Moter, Annette; Loddenkemper, Christoph; Jansen, Andreas; Tandler, Rene; Morguet, Andreas J.; Fenollar, Florence; Raoult, Didier; Bogdan, Christian; Schneider, Thomas (Journal of Clinical Microbiology, 2012)
"Classical" Whipple's disease (cWD) is caused by Tropheryma whipplei and is characterized by arthropathy, weight loss, and diarrhea. T. whipplei infectious endocarditis (TWIE) is rarely reported, either in the context of cWD or as isolated TWIE without signs of systemic infection. The frequency of TWIE is unknown, and systematic studies are lacking. Here, we performed an observational cohort study on the incidence of T. whipplei infection in explanted heart valves in two German university centers. Cardiac valves from 1,135 patients were analyzed for bacterial infection using conventional culture techniques, PCR amplification of the bacterial 16S rRNA gene, and subsequent sequencing. T. whipplei-positive heart valves were confirmed by specific PCR, fluorescence in situ hybridization, immunohistochemistry, histological examination, and culture for T. whipplei. Bacterial endocarditis was diagnosed in 255 patients, with streptococci, staphylococci, and enterococci being the main pathogens. T. whipplei was the fourth most frequent pathogen, found in 16 (6.3%) cases, and clearly outnumbered Bartonella quintana, Coxiella burnetii, and members of the HACEK group (Haemophilus species, Actinobacillus actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae). In this cohort, T. whipplei was the most commonly found pathogen associated with culture-negative infective endocarditis. Copyright © 2012, American Society for Microbiology. All Rights Reserved.
CRIS-Team Scopus Importer:2024-02-26